Cymbochasma borysthenica (Pall. ex Schlecht.) Klokov et Zoz в Україні - БОЙКО, ПАВЛО МИХАЙЛОВИЧ (CHORNOMORSKI BOTANICAL JOURNAL, 2005)
Cymbochasma borysthenica (Pall. ex Schlecht.) Klokov et Zoz в Україні